Subunit P60 of phosphatidylinositol 3-kinase promotes cell proliferation or apoptosis depending on its phosphorylation status. - Yu-Qin Di; Yu-Meng Zhao; Ke-Yan Jin; Xiao-Fan Zhao (PLoS Genetics, 2021)
The regulatory subunits (P60 in insects, P85 in mammals) determine the activation of the catalytic subunits P110 in phosphatidylinositol 3-kinases (PI3Ks) in the insulin pathway for cell proliferation and body growth. However, the regulatory subunits also promote apoptosis via an unclear regulatory mechanism. Using Helicoverpa armigera, an agricultural pest, we showed that H. armigera P60 (HaP60) was phosphorylated under insulin-like peptides (ILPs) regulation at larval growth stages and played roles in the insulin/ insulin-like growth factor (IGF) signaling (IIS) to determine HaP110 phosphorylation and cell membrane translocation; whereas, HaP60 was dephosphorylated and its expression increased under steroid hormone 20-hydroxyecdysone (20E) regulation during metamorphosis. Protein tyrosine phosphatase non-receptor type 6 (HaPTPN6, also named tyrosine-protein phosphatase corkscrew-like isoform X1 in the genome) was upregulated by 20E to dephosphorylate HaP60 and HaP110. 20E blocked HaP60 and HaP110 translocation to the cell membrane and reduced their interaction. The phosphorylated HaP60 mediated a cascade of protein phosphorylation and forkhead box protein O (HaFOXO) cytosol localization in the IIS to promote cell proliferation. However, 20E, via G protein-coupled-receptor-, ecdysone receptor-, and HaFOXO signaling axis, upregulated HaP60 expression, and the non-phosphorylated HaP60 interacted with phosphatase and tensin homolog (HaPTEN) to induce apoptosis. RNA interference-mediated knockdown of HaP60 and HaP110 in larvae repressed larval growth and apoptosis. Thus, HaP60 plays dual functions to promote cell proliferation and apoptosis by changing its phosphorylation status under ILPs and 20E regulation, respectively.